2009
DOI: 10.1167/iovs.08-2759
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Optical Density Ratios in Subretinal Fluid as a Clinically Relevant Biomarker in Exudative Macular Disease

Abstract: Results suggest that CMM may correlate with BCVA at BSL, but has limited predictive value regarding recovery of visual function. Most interesting, ODR correlated with BCVA under therapy and was the only parameter that was pathognomic for nAMD in contrast to CSC in this study. ODR may reflect the status of the blood-retina barrier and may be used for pathophysiologic differentiation and prognostic purposes in exudative macular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 15 publications
2
40
1
1
Order By: Relevance
“…While Ahlers et al showed highly significant differences in OD measurements between CSR and AMD, 5 we can speculate only as to why we detected no such differences in our patients. One reason might be the different OCT instruments used: the Cirrus spectral domain OCT in the study of Ahlers et al 5 versus the SPECTRALIS spectral domain OCT in our study.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…While Ahlers et al showed highly significant differences in OD measurements between CSR and AMD, 5 we can speculate only as to why we detected no such differences in our patients. One reason might be the different OCT instruments used: the Cirrus spectral domain OCT in the study of Ahlers et al 5 versus the SPECTRALIS spectral domain OCT in our study.…”
Section: Discussioncontrasting
confidence: 83%
“…Our current study did not look into the possibility of whether changes in OD within specific disease states correlate with prognosis, as was done with neovascular AMD in an earlier study by Ahlers et al 5 More data on the development and clinical course of diseases and changes in OD are needed to determine the relationship between altered OD and prognosis.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The fl uid can be recorded by SD-OCT as a hyporefl ective area which is homogenous when it begins and can get denser and gain refl ectivity as it persists. SRF is assumed to become increasingly toxic as it gains refl ectivity, impairing recovery of visual acuity [ 13 ]. SRF is usually either dome-shaped or fl at, but when associated with a PED appears as a triangular shape on OCT B-scans surrounding the PED to form a ring around it [ 12 ].…”
Section: Sd-oct In Namdmentioning
confidence: 99%